Analisis Pengaruh Persepsi Konsumen Terhadap Keputusan Pembelian Sepeda Motor Honda Matic Di Dealer Prima Motor Pasir pengaraian - Andi Afrizal., Asra Yurita, Makmur, (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2017)
The purpose of this study was to determine the influence of consumer perception towards the purchase decision of Honda motorcycles Prima Motor Dealer matic in Pasir Pengaraian. The population in this study is the consumer of Prima Motor Dealer Sand Pengaraian. The research sample using accidental sampling technique, with a total of 98 people. The independent variables in this study consumer perception (X), the dependent variable (Y) purchasing decisions. Methods of data collection using field research and library research, field research consisted of observationsand questionnaire. Based on simple linear regression analysis results obtained yield was 0.895, indicating consumer perception has a significant influence on purchasing decisions Honda motorcycles Prima Motor Dealer matic in Pasir Pengaraian and have a positive influence. The result of the calculation of the coefficient of determination is 37.4%, which means that perception influence consumer purchasing decisions by 37.4%, while the remaining 62.6% is influenced by other variables not examined in this study. The conclusion of the study is the result of data analysis using simple linear regression, showing the strength of the relationship between perceptions of consumers with purchasing decisions, which correlates positively by 0.895. From the calculation results of hypothesis testing showed t_hitung greater than T_ (table) that T_ (count) 7,531> 1,661sehingga hypothesis that there is significant influence consumer perceptions of acceptable purchase decision.